2019
DOI: 10.1111/hepr.13393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of new prognostic systems for patients with resectable hepatocellular carcinoma: Albumin‐Bilirubin grade and Albumin‐Indocyanine Green Evaluation grade

Abstract: Aim We aimed to compare the prognostic abilities of two novel liver function‐estimating models, Albumin‐Bilirubin (ALBI) and Albumin‐Indocyanine Green Evaluation (ALICE) grades, in patients with hepatocellular carcinoma. Methods Data of 1270 patients who underwent initial hepatectomy for hepatocellular carcinoma between 1986 and 2016 were retrospectively collected from a multi‐institutional database. The prognostic impact of each system was analyzed according to the results of the area under the receiver opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Invasive surgery, such as intraoperative and postoperative bleeding and longer operation time was also well-established risk factors for high morbidity and poor survival among patients with colorectal liver metastases and hepatocellular carcinoma [ 21 25 ]. ALBI score was well-known as a predictive factor of posthepatectomy liver failure and poor outcomes [ 26 , 27 ]. In our study, ALBI score had no relation with surgery-related DIC and high CCI.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive surgery, such as intraoperative and postoperative bleeding and longer operation time was also well-established risk factors for high morbidity and poor survival among patients with colorectal liver metastases and hepatocellular carcinoma [ 21 25 ]. ALBI score was well-known as a predictive factor of posthepatectomy liver failure and poor outcomes [ 26 , 27 ]. In our study, ALBI score had no relation with surgery-related DIC and high CCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tumor-associated variables and liver function have been strongly related to longterm prognosis. Honmyo et al [10] reported that the albumin-bilirubin grade and albumin-indocyanine green evaluation grade were not only independent prognostic factors but also associated with postoperative complications. Preoperative nutritional status and immunological status were associated with postoperative complications and outcomes of patients with HCC such as obesity, Glasgow Prognostic Score (GPS) score, and neutrophil-to-lymphocyte ratio (NLR) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…That is, it includes several subjective items (ascites and encephalopathy) and interrelated items (ascites and serum albumin) [12]. After the introduction of the ALBI grading system, the good predictability of the ALBI grading system was confirmed in LC patients, irrespective of liver disease etiologies or the presence of hepatocellular carcinoma (HCC) in numerous clinical studies [13,14,15,16,17,18,19,20,21,22]. However, to our knowledge, the relationship between ALBI grade and npRQ in chronic liver disease (CLD) patients is largely unknown.…”
Section: Introductionmentioning
confidence: 99%